Collaborative Governance in the Development of Singhasari Special Economic Zone - Shinta Fatimah Durrety (University of Merdeka Malang, 2024)
The SEZ Singhasari, established through Government Regulation No. 68 of 2019, was targeted to be operational by 2022, and on October 11, 2022, it was declared ready to receive investors. However, empirically, SEZ Singhasari experienced slight delays in its readiness compared to other SEZs in general, indicating a lack of effectiveness in the collaborative relationship between the government and various other actors in accelerating the operation of SEZ. Based on this background, the research problem is framed around understanding and addressing the challenges and dynamics associated with the Collaborative Governance Model in the development of the Special Economic Zone (SEZ) Singhasari, to identify the initial conditions, facilitative leadership, institutional design, and analyzing the collaborative process and interim results in the development of SEZ Singhasari. This research adopts a descriptive qualitative approach with Singosari District as the selected location. The data sources for this research include primary and secondary data, collected through interviews, observations, and documentation. The research instruments used are the researcher, interview guidelines, field notes, and supporting tools. The data analysis follows Creswell's method of data analysis and is tested through source triangulation and data collection technique triangulation. Despite power and resource imbalances among actors, collaboration is facilitated due to mutual interdependence. Face-to-face dialogues through incidental coordination meetings are employed in the collaborative process, emphasizing communication, trust, and consensus in decision-making. The regulations and the establishment of the SEZ Singhasari Operationalization Acceleration Team support coordination and institutional design. SEZ Singhasari has implications for students and the surrounding community, enhancing land valuation and economic activities. These impacts strengthen collaboration and drive stakeholders toward achieving their planned goals.